Vestibular contribution to spatial encoding - Zanchi, Silvia; Cuturi, Luigi F.; Sandini, Giulio; Gori, Monica; Ferrè, Elisa R. (The European journal of neuroscience, 2023)
Determining the spatial relation between objects and our location in the surroundings is essential for survival. Vestibular inputs provide key information about the position and movement of our head in the three‐dimensional space, contributing to spatial navigation. Yet, their role in encoding spatial localisation of environmental targets remains to be fully understood. We probed the accuracy and precision of healthy participants' representations of environmental space by measuring their ability to encode the spatial location of visual targets (Experiment 1). Participants were asked to detect a visual light and then walk towards it. Vestibular signalling was artificially disrupted using stochastic galvanic vestibular stimulation (sGVS) applied selectively during encoding targets' location. sGVS impaired the accuracy and precision of locating the environmental visual targets. Importantly, this effect was specific to the visual modality. The location of acoustic targets was not influenced by vestibular alterations (Experiment 2). Our findings indicate that the vestibular system plays a role in localising visual targets in the surrounding environment, suggesting a crucial functional interaction between vestibular and visual signals for the encoding of the spatial relationship between our body position and the surrounding objects.